THE ROLE OF INFORMATION TECHNOLOGY IN DEVELOPING INVESTIGATION AND MONITORING PROCEDURES IN JORDANIAN CRIMINAL LAW - Dr. Thamer yousef salem Al-maiah (Scholar Express Journals, 2023)
Scientific progress clearly affects the reality it encounters. This tremendous development that follows the communications system has had a great impact on reality and the law with regard to crimes, to the point that they have become of a special nature in terms of the means by which they are committed on the one hand and on the other hand the location in which they are located and in terms of the perpetrators who commit to them, until there has become a partnership between artificial intelligence and artificial intelligence. Human. Legislation has tried to benefit from technology by searching for alternatives to short-term custodial punishments in many contemporary penal systems, and shedding light on electronic monitoring as one of those alternative punishments, where the convict can carry out his sentence outside the penal institution through electronic monitoring, and thus we eliminate On the disadvantages resulting from his presence in the penal institution
Keywords: Investigation procedures; surveillance; electronic inspection